Surface charge density of rat blood erythrocytes under the influence of millimeter diapason electromagnetic radiation - Nerkararyan, A. V.; M. S. Mikaelyan; M. A. Shahinyan; P. O. Vardevanyan (ՀՀ ԳԱԱ հրատ.)
﻿In present work the effect of millimeter electromagnetic radiation on the surface charge density of rat blood erythrocytes has been studied. The experiments were carried out irradiating suspension of erythrocytes of rat blood by different frequencies. It was shown that in the case of the irradiation by water non-resonant as well as resonant frequencies the value of studying parameter decreases compared to control samples. In the case of the irradiation by water resonant frequency the decrease of the value of studying parameter is more pronounced. In both cases a reliable changes of the surface charge density value of rat blood erythrocytes take place.﻿Ուսումնասիրվել է միլիմետրային էլեկտրամագնիսական ճառագայթման ազդեցությունը առնետների արյան էրիթրոցիտների մակերևութային լիցքի խտության վրա: Ուսումնասիրություններն կատարվել են առնետների արյան էրիթրոցիտների կախույթը ճառագայթելով տարբեր հաճախություններով: Ցույց է տրվել, որ ջրի համար ոչ ռեզոնանսային և ռեզոնանսային հաճախություններով ճառագայթահարման դեպքում ուսումնասիրվող պարամետրի արժեքը նվազում է ստուգիչ նմուշների համեմատ: Ջրի համար ռեզոնանսային հաճախությամբ ճառագայթահարելու դեպքում այդ պարամետրի արժեքի նվազումն ավելի վառ է արտահայտված: Երկու դեպքում էլ տեղի են ունենում առնետների արյան էրիթրոցիտների մակերևութային լիցքի խտության արժեքի էական փոփոխություններ: ﻿Исследовалось влияние миллиметрового электромагнитного излучения на плотность поверхностного заряда крови эритроцитов крыс. Эксперименты осуществлялись облучeнием суспензии эритроцитов крови крыс разными частотами. Показано, что в случае облучения не резонансными и резонансными для воды частотами значение исследуемого параметра уменьшается по сравнению с контролем. В случае облучения резонансной для воды частотой уменьшение значения исследуемого параметра выражено более ярко. В обоих случаях имеют место достоверные изменения значения плотности поверхностного заряда эритроцитов крови крыс.
Keywords: Biology; Molecular Biology